Commercial coconut palm as an ecotope of Chagas disease vectors in north-eastern Venezuela - A. Morocoima; J. Chique; R. Zavala-Jaspe; Z. Díaz-Bello; E. Ferrer; S. Urdaneta-Morales; L. Herrera (Journal of Vector Borne Diseases, 2010)
Background & objective: There are few reports of Coccus nucifera (Palmae) infestation by triatomines (Hemiptera, Reduviidae, Triatominae), vectors of Trypanosoma cruzi (Kinetoplastida: Trypanosomatidae), the causal agent of American Trypanosomiasis. The aim of this study was to determine if this palm is an appropriate ecotope for Rhodnius prolixus and Triatoma maculata, the main vectors in Venezuela. Methods: Dry and green leaves, humid debris, interfoliaceus meshes and bracts from C. nucifera from north-eastern Venezuela were examined for the presence of triatomines. Samples of the intestinal content of vectors, macerated in isotonic saline solution and haemolymph were examined microscopically for the presence of Trypanosoma spp. The parasites were isolated and characterized using biological parameters and PCR. Triatomine blood meal sources were determined using ELISA. Results: A total of 14 palms were examined in which viable eggs of both species of vectors were found in 13 palms (92.85%). A total of 242 R. prolixus and 144 T. maculata adults were collected, of which 98% of R. prolixus and 70% of T. maculata individuals were infected by T. cruzi (TcI genotype) and 13% of R. prolixus individuals showed a mixed infection with T. rangeli, the other American trypanosome. ELISA testing for possible triatomine blood-meal sources revealed that these vectors are essentially eurytrophic and zoophilic, although R. prolixus also eventually used human blood as a nourishment source. Interpretation & conclusion: The results obtained suggest that C. nucifera is an appropriate vegetal niche for these triatomine species in Venezuela. The presence of this commercial palm may represent a useful environmental bioindicator of risk for Chagas disease.